Innovation-Driven Development of Ukraine’s Agriculture Under Complex Threats - GONCHARENKO, O.; ANISHCHENKO, V.; SIRENKO , K. (Science and Innovation, 2024)
Introduction. As a result of Russia's full-scale war against Ukraine, food security at the global level is under threat. Ukraine’s agricultural sector suffered losses of USD 2.1 billion because of the destruction or partial damage of agricultural lands and failure to harvest crops. Agricultural land has been damaged by landmine contamination, unexploded ammunition, which poses a mortal threat to farmers, and by direct physical bombardment of agricultural land. Problem Statement. Production and productivity sustainability of agricultural production is one of the most important issues today. A system of knowledge and innovation in the agricultural sector is necessary and important. It includes organizations and cooperatives of farmers, foresters, advisers, researchers, business representatives, and public organizations. Purpose. The purpose is to conduct a correlation-regression analysis of the innovation-driven development of agriculture in Ukraine under conditions of complex threats. Material and Methods. While doing this study we have used methods of multivariate statistical analysis and taxonomy methods to assess the level of individual threats. The center of gravity method is used to select representative indicators of threats to innovation-driven development. Results. In the study, the complex threats to the innovation-driven development of agriculture have been analyzed. The matrix of distances has been calculated for the initial set of indicators characterizing a separate threat. The threat of a decrease in research and development expenditure in the forecast period has the highest impact on the level of innovation-driven development of agriculture. This is evidenced by low pairwise correlation coefficients and the overall level of innovation-driven development. Conclusions. The correlation-regression analysis of innovation-driven development of agriculture has made it possible to determine the highest threat affecting the level of innovation-driven development of agriculture.